ANALISIS PENDAPATAN RUMAH TANGGA PETANI DAN KEBERLANJUTAN REPONG DAMAR DI KECAMATAN PESISIR TENGAH KABUPATEN PESISIR BARAT - Fibriand Andika; Dwi Haryono; Sumaryo Gitosaputro (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This study aimed to determine forming income, the income of farmer households, and the sustainability of repong damar at Pahmungan Village, Central Pesisir Subdistrict, West Pesisir District. The method used in this research was the survey method. Primary and secondary data were collected in this study. The Sampling used census sampling. The number of respondents consisted of 58 farmers of repong damar. This study took approximately two months, starting from March to April 2018. The results of this study indicate that repong damar farming provides benefits and was feasible to run based on the results of the R/C has a value of>1. The household income of repong damar farmers was IDR 48,657,130.03 per year, the largest contribution comes from on-farm income with a percentage of 85.10 percent. Repong damar farming at Pahmungan Village, Central Pesisir Subdistrict, West Pesisir District was considered sustainable from social, ecological, and economic aspects.Key words: household income, income, repong damar, sustainability.